Lightning-induced effects in electrical and telecommunication systems - Baba, Yoshihiro; Rakov, Vladimir A., 1955- (The Institution of Engineering and Technology, 2020)
Providing an overview of modelling and understanding lightning-related effects on complex power and telecommunications systems, this book explores both traditional transmission-line theory as well as the state-of-the art finite difference time-domain (FDTD) method.
Keywords: Electric power systems -- Reliability -- Mathematical models.; Electric power systems -- Protection.; Lightning.; Electric apparatus and appliances -- Protection.; Telecommunication systems -- Reliability -- Mathematical models.; Telecommunication systems -- Protection.; elektronické knihy; electronic books